Enhancing beam structural damage detection using spectral moment values and spectral moment cumulative function models - Thanh Q Nguyen; Thuy T Nguyen; Phuoc T Nguyen (Journal of Low Frequency Noise, Vibration and Active Control)
Evaluation and identification of structural damage play a crucial role in ensuring the safety and reliability of structures. This study explores the application of spectral moment value analysis as a robust tool to assess and detect structural damage. Spectral moment values provide detailed information on how a structure responds to load, helping to accurately identify the location, type, and extent of the damage. By monitoring changes in spectral moment values using experimental data on damaged and undamaged steel beams under moving loads, early signs of hidden damage can be detected, allowing timely implementation of repair or maintenance measures before the condition worsens. Moreover, spectral moment value analysis supports the evaluation of structural reliability based on load bearing capacity and resistance to damage, aiding in decision-making processes regarding the repair, improvement, or replacement of the structure. The methodology used in this research provides a cost-effective and efficient approach to the evaluation and identification of structural damage, with potential applications in various engineering fields.